A 44 Year Old Man with Chronic Myeloid Leukemia and Mass at Right Lower Leg - Islamiah, Ahadini; Wardhani, Shinta Oktya (Fakultas Kedokteran Universitas Brawijaya, 2017)
Chronic myeloid leukemia (CML) is a clonal myeloproliferative disorder of primitive hematopoetic stem cells that is characterized by overproduction of myeloid series cells, splenomegaly, and leukocytosis. We reported a case of 44 years old male with CML who complained about swelling right leg and pain for 3 month. It had been diagnosed as CML for 3 years, and he took hydroxyurea but stopped for a year due to economic problem. The results of clinical examination, laboratory, biopsy, and radiology showed a result matched to CML with soft tissue mass. The results of Fine Needle Aspiration Biopsy (FNAB) of fragmented histiocytes leg mass, multinucleated giant cells, and atypical nucleated with a possibility of fibroma with atypical nucleated cells. Magnetic resonance imaging (MRI) showed multilocular lobulated soft tissue mass from the popliteal region to the cruris dextra, cyst mass high protein dd/solid tumor with vascular encasement and lesions in bone marrow replacement, and fluid collection on bursa parapatella. The patient was treated with hydroxyurea and showed clinical improvement and decreased mass size in the legs.